2017
DOI: 10.1111/and.12834
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A induced oxidative stress and apoptosis in mice testes: Modulation by selenium

Abstract: Spermatogenesis, a highly coordinated process, is prone to environmental insults which may lead to impaired spermatogenesis or, at worst, infertility. Bisphenol A (BPA) is a well-known global environmental toxicant and a ubiquitous oestrogenic chemical. This study evaluated the role of selenium (0.5 ppm sodium selenite/kg diet) on spermatogenesis after BPA treatment in different groups of male BALB/c mice: control, selenium, BPA and selenium+BPA. Markers of oxidative stress and apoptosis were evaluated in test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 39 publications
7
60
0
Order By: Relevance
“…animals. Similar observations were reported by previous studies (Kaur, Saluja, & Bansal, 2018;Sudha, 2011;Yeh et al, 2009) in which severe vacuolization of spermatozoa in seminiferous tubules was observed upon BPA exposure. However, HEMKLE administration to BPA-treated mice maintained the normal germ cells population and less vacuolization in Group IV (HEMKLE + BPA).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…animals. Similar observations were reported by previous studies (Kaur, Saluja, & Bansal, 2018;Sudha, 2011;Yeh et al, 2009) in which severe vacuolization of spermatozoa in seminiferous tubules was observed upon BPA exposure. However, HEMKLE administration to BPA-treated mice maintained the normal germ cells population and less vacuolization in Group IV (HEMKLE + BPA).…”
Section: Discussionsupporting
confidence: 92%
“…Histological analysis of testes from all the treatment groups revealed that in Group III (BPA) animals, there was severe vacuolization and displacement by some fibrinoid debris in seminiferous tubules when compared to Group I (Control) and Group II (HEMKLE) animals. Similar observations were reported by previous studies (Kaur, Saluja, & Bansal, ; Sudha, ; Yeh et al, ) in which severe vacuolization of spermatozoa in seminiferous tubules was observed upon BPA exposure. However, HEMKLE administration to BPA‐treated mice maintained the normal germ cells population and less vacuolization in Group IV (HEMKLE + BPA).…”
Section: Discussionsupporting
confidence: 91%
“…BPA at low doses decreases the synthesis of estradiol and inhibits the growth of antral follicles isolated from wild-type and Ahr knock-out mice, through partial involvement of the aryl hydrocarbon receptor pathway [32]. BPA exposure results in decreased sperm counts and motility, and increased ROS and lipid peroxidation in mice testes [25] (Table 3).…”
Section: Endocrine Disruption and Reproductive Abnormalitiesmentioning
confidence: 99%
“…Bisphenol A (BPA) is a synthetic oestrogen and an environmental toxicant which is present in innumerable consumer products and considered as highest utilising industrial chemicals worldwide (Alboghobeish et al, 2019). Humans and wildlife are widely and critically exposed to BPA due to its extensive use for the production of water pipes, drinking containers, dental monomers, medical equipments, etc (Kaur, Saluja, & Bansal, 2018). Worldwide 400 million tonnes of plastics produces annually and roughly 3.5 million tons was manufactured in 2008 (Goncalves, Semprebon, Biazi, Mantovani, & Fernandes, 2018).…”
mentioning
confidence: 99%
“…Due to advancement in industrial and manufacturing activities, BPA is becoming ubiquitous in our living environment and have raised various public health concerns (Wu et al, 2018). Animal-based studies have reported that BPA exposure exerts undesirable effects on male reproductive system by altering the expression of genes associated with spermatogenesis and endocrine disruption (Kaur et al, 2018). Another study by Shirani, Alizadeh, Mahdavinia, and Dehghani (2019), showed a marked reduction in the levels of reduced glutathione and catalase whereas elevation in mitochondrial reactive oxygen species (ROS) and lipid peroxidation (LPO) levels along with mitochondrial membrane damage was observed upon BPA administration in rats.…”
mentioning
confidence: 99%